Optimisation and characterisation of biodiesel from biodegradation of organic wastes by black soldier fly larvae - Syukriyah Ishak (Tanjong Malim, 2020)
Optimisation and characterisation of biodiesel from biodegradation of organic wastes by black soldier fly larvae by Syukriyah Ishak